SOSIALISASI PERTOLONGAN PERTAMA CEDERA OLAHRAGA DAN PELAYANAN FISIOTERAPI PADA PERKUMPULAN BULU TANGKIS DI DENPASAR - Nugraha, M.H.S.; Tianing, N.W.; Winaya, I.M.N.; Saraswati, N.L.P.G.K. (Buletin Udayana Mengabdi, 2023)
Sport is a very important physical activity and is closely related to human life. A significant increase in players or athletes, if not accompanied by knowledge of playing techniques and handling initial injuries on the field, can result in athletes having a tendency to re-injury and slow recovery, so that the expected achievements cannot be realized. Based on these problems, community service was carried out with solutions: (1) Socialization of the handling of sports injuries preventions, (2) physical examination of core muscle endurance, footwork, and balance, and (3) socialization of stretching, muscle strength, and injury prevention training that targets the core muscle and prorioceptive areas. The socialization was carried out through leaflet media and direct face-to-face presentations to 55 athletes. Meanwhile, at the stage of measuring physical capacity, it is carried out using inclusion and exclusion criteria in order to meet the requirements for the validity and reliability of the measurements that have been determined, reaching 25 athletes. The results of static balance are dominated by the very good category, while the foot work is dominated by the moderate category. In core muscle endurance the average athlete reaches (87.12 ± 38, 23), while in dynamic balance the average score of the athlete reaches (94.24 ± 11, 35). Keywords: badminton, first aid, physiotherapy, sports injury